Meningkatkan Aktivitas dan Hasil Belajar IPS dengan Model PBL, GI dan PAP di Sekolah Dasar - Helda Nur Ariyanti; Ahmad Muhyani Rizalie (Lembaga Pengembangan Kinerja Dosen, 2023)
The problem in this study is the low activity and learning outcomes of students in IPS (Social Studies). This happens because the teaching method is only one-way, still using conventional methods, and students tend to be passive. The way to overcome this problem is through the use of Problem Based Learning (PBL), Group Investigation (GI), and Picture And Picture (PAP) models. The research aims to improve student activity and learning outcomes. This research focused on fifth grade students at SDN Teluk Tiram 2 Banjarmasin, which numbered 20 people, in the form of 12 boys and 8 girls. This research method applies a qualitative approach that uses the type of Classroom Action Research (CAR). Qualitative data were obtained from observations of educator and student activities, while quantitative data were obtained from individual written test results. The results of this study show that at the fourth meeting, the teacher's activity obtained a score of 26, rated as